The influence of confining stress on optimum spacing of TBM cutters for cutting granite. (October 2016) - Liu, Jie; Cao, Ping; Han, Dongya
Abstract: Two series of indentation tests on a triaxial testing machine with groove morphology measurement were conducted to investigate the effect of confining stresses on the optimal spacing among TBM cutter indentations. In the first series of indentation tests, over breaking, moderate breakages that resulted from effective fracture interactions and insufficient breaking between indentations were encountered with the increase in spacing. An analysis on the groove volumes and consumed energy indicates that longer spacing is favorable when the differential stress increases, whereas the opposite occurs when the differential stress decreases. To confirm these conclusions, another series of indentation tests was conducted for the spacing and indentation depth of 70 mm and 6 mm, respectively. The results show that the fiercer propagation of surface cracks and more effective connections of the internal cracks are responsible for the elongated optimal spacing when the differential stress increases; the optimal spacing is shortened because of the restrained surface propagation by decreasing the differential stress. Highlights: Successive indentations in a biaxial stress state by the TBM cutter are conducted on granite samples. Groove morphologies and crack propagations have been investigated. The effects of confining stress on optimal spacing have been analyzed. The effects of confining stress on rock breakages when spacing and indentation depths are fixed have been investigated.